Irreversible electroporation for prostate cancer using PSMA PET-CT - Dongho Shin; Chang Eil Yoon; Hyeok Jae Kwon; Hyong Woo Moon; Yong Hyun Park; Hyuk Jin Cho; U-syn Ha; Sung-Hoo Hong; Sonya Youngju Park; Seunggyun Ha; Joo Hyun O; Ie Ryung Yoo; et al. (Prostate International, 2023)
Background: To demonstrate the clinical usefulness of prostate-specific membrane antigen (PSMA) positron emission tomography (PET) computerized tomography (CT) for irreversible electroporation (IRE) in prostate cancer patients. Methods: From January to May 2021, 17 men were diagnosed with localized prostate cancer through preoperative mpMRI and [18F] florastamin PSMA PET-CT imaging, followed by transperineal MRI-ultrasound fusion-guided biopsy. The patients underwent IRE focal therapy at the target lesions under general anesthesia. To evaluate the treatment outcome, serum prostate-specific antigen (PSA) levels were followed up in the 1st, 3rd, 6th, 9th, 12th months, and mpMRI was taken in the 1st and 12th months, followed by MR fusion biopsy in the 12th month post-IRE. Results: The mean age of the patients was 66.1 ± 9.3 with a median PSA of 7.5 ng/ml. After the treatment, PSA nadir was 4.06 ± 3.4, and 11 (64.7%) achieved decline of PSA more than 50% from the baseline. Rate of negative biopsy for prostate cancer is 88% (15/17) at 12 months MR fusion biopsy after the IRE treatment. Among the relapsed cases, 1 (6.9%) patient recurred at margin of treated area, and 1 (6.9%) patient was from outfield recurrence. When excluding initial four patients, none of the patients had cancer recur. Conclusions: When treating with IRE focal therapy, PSMA-PET CT is a potentially valuable diagnostic approach for localizing prostate cancer; it supports the detection of lesions with conventional mpMRI, enabling to perform the procedure more completely.